Challenges on the way to stage three of European Monetary Union - Christa Randzio-Plath (Intereconomics, 1995)
While the Maastricht Treaty envisages a single European Currency as part of the Economic and Monetary Union, it contains no detailed instructions as to the practical arrangements for its introduction. Despite prolonged discussions and negotiations at various levels, no consensus has so far been achieved on the optimum changeover procedure. This article deals with some of the major challenges in this context.
Keywords: 330; European Union